Oxidative Stress as a Main Contributor of Retinal Degenerative Diseases - Isabel Pinilla; Victoria Maneu (Antioxidants, 2022)
Retinal degenerative diseases, including inherited retinal dystrophies (IRDs) and acquired multifactorial diseases, such as age-related macular degeneration (AMD), diabetic retinopathy (DR) or ganglion cell damage secondary to glaucoma or other pathologies, are the main causes of blindness in developed countries [...]